Gamified Student Activity Transcript System using MDA Framework - Ezekiel Pradipta Nursetyo Reginanda; Wahyu Andi Saputra; Ariq Cahya Wardhana; Rifki Adhitama (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Universities increasingly recognize that employability and civic competencies are formed not only through formal coursework but also through co-curricular and extracurricular engagement. In many campuses, however, activity reporting remains fragmented, highly manual, and submitted late, which results in verification bottlenecks and incomplete student records. This study develops a web-based Student Activity Transcript (SAT) application to support end-to-end submission, verification, and accumulation of student activity points. A gamification approach is embedded to reduce reporting friction and sustain participation. The design follows the Mechanics–Dynamics–Aesthetics (MDA) framework so that each game element is justified from rules to run-time interaction patterns and the intended user experience. The system is implemented using a PHP web framework and a relational database, and it integrates role-based workflows for students, academic advisers, and student affairs administrators. Functional validation is performed through specification-based (black-box) testing to confirm that critical workflows—registration, login, activity submission, verification, and transcript generation—operate as intended. The resulting artifact demonstrates a reusable pattern for universities that need to digitize activity transcripts while ensuring that gamification is applied in a structured, theory-informed manner. This work contributes to TAK governance workflow that preserves institusional verification while adding engagement loops, and an implementation and test blueprint that can be adapted to other campuses adopting transcript or digital badge recognition system.